N??(?, I)- Ward Continuity - Sengul, Hacer; Cakalli, Huseyin; Et, Mikail (Amer Inst Physics, 2019)
The main purpose of this paper is to introduce the concept of strongly ideal lacunary quasi-Cauchyness of order (alpha, beta) of sequences of real numbers. Strongly ideal lacunary ward continuity of order (alpha, beta) is also investigated. Interesting results are obtained.
International Conference of Mathematical Sciences (ICMS) -- JUL 31-AUG 06, 2018 -- Maltepe Univ, Istanbul, TURKEY
Keywords: Sequences; series; summability; functional analysis